If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -10 = 4x + 6 Reorder the terms: -10 + 5x = 4x + 6 Reorder the terms: -10 + 5x = 6 + 4x Solving -10 + 5x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -10 + 5x + -4x = 6 + 4x + -4x Combine like terms: 5x + -4x = 1x -10 + 1x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 -10 + 1x = 6 + 0 -10 + 1x = 6 Add '10' to each side of the equation. -10 + 10 + 1x = 6 + 10 Combine like terms: -10 + 10 = 0 0 + 1x = 6 + 10 1x = 6 + 10 Combine like terms: 6 + 10 = 16 1x = 16 Divide each side by '1'. x = 16 Simplifying x = 16
| 2m-t=5m+5 | | 4-X=2X-3X+1 | | 130=-5(3x-5) | | 7x+9=49x^2+126x+81 | | 5X+X=6X+3 | | 2x-y+6z=20 | | x+7-2=3x | | 4-6x+8=1-5x-4 | | 8=3h+5 | | (0-k)(1-k)=0 | | 2x^2+10+52=0 | | (X+3)+2(X-4)=5(X+3) | | (0-k)(0-k)=0 | | X+2x+2x-30=140 | | 9(x+8)+12=8(x+18)+10 | | Y=-3x*2 | | Y=4x^2+3x | | 2=2x-6x+3x+9 | | 360-65-x=44 | | q=40+-0.5p | | 3+4(2x+5)=39 | | 48/6= | | x^2+30x-40=0 | | 5x+5=52 | | 4-293x-4=1-(5x+4) | | 0+50*1-60-60*0+10=C | | q=40-0.5p | | -100+82=x | | 4(5x-1)-10x=3 | | -6x-3.4=3x+.2 | | -70-(-58)=x | | x^2+12x+56=0 |